Integrated DNA Barcoding and Morphometric Characterization of Palm Weevils (Rhynchophorus spp.) in North Sulawesi - Balansa, Endrile Golmen; Salaki, Christina Leta; Tarore, Dantje; Mamahit, Juliet Merry Eva; Kolondam, Beivy Jonathan; Tallei, Trina Ekawati (Bogor Agricultural University, Indonesia, 2025)
Palm weevils (Rhynchophorus spp.) are significant pests of sago palms worldwide. Yet, the taxonomy and evolutionary lineage of these species in North Sulawesi remain unclear, likely due to geographic isolation driving genetic variation and species differentiation. This study aimed to investigate the genetic diversity and morphological differentiation of Rhynchophorus across distinct geographic regions in North Sulawesi using an integrative approach combining DNA barcoding and morphometric analysis. Morphometric traits from palm weevil specimens collected in Sangihe Island, Minahasa, and Bolaang Mongondow were measured and statistically analyzed using one-way ANOVA, MANOVA, principal component analysis (PCA), and linear discriminant analysis (LDA) to assess interpopulation morphological differences. For molecular identification, the cytochrome oxidase I (COI) gene was amplified and sequenced. Phylogenetic relationships were inferred using the maximum likelihood method, and a DNA barcode gap analysis was conducted to evaluate the separation between intra- and interspecific genetic distances. Morphometric analysis revealed significant size variations among the specimens, particularly in rostrum dimensions, with the EBBM (Bolaang Mongondow) group showing the highest values. COI-gene-based identification confirmed that all specimens were of R. vulneratus. However, phylogenetic analysis showed EBMin (Minahasa) and EBBM forming a distinct subgroup, while EBMan, EBSTS, EBTam, and EBSTU (all from Sangihe Island) clustered separately. Barcode gap analysis demonstrated a clear distinction between intra- and interspecific divergence, validating COI as a reliable marker for species delimitation. This study concludes that integrating morphometric and genetic analyses reveals geographic structuring within R. vulneratus, highlighting the effectiveness of combined methods for accurate identification and population differentiation.